Exploring the Effects of Establishing a Psychiatric Ward in Hatyai Regional Hospital - Thepchatri, Chaiyasit; Sangkaew, Sorawat; Tamviriyakul, Hathaitip; Wanliang, Thanyalak; Prayoonsawatdat, Wilawan; Petcharut, Siwawong; Kongrueang, Pawanrat; Khongpaitoon, Chada; Kasoh, Khodeeyoh (Journal of Health Science of Thailand, 2024)
Mental health disorders and substance abuse in Thailand heavily strain healthcare resources. Psychiatric wards in general hospitals improve access to comprehensive care, but their effect on patient outcomes and healthcare system efficiency in Thailand remains underexplored. This study aimed to compare patient demographics, clinical characteristics, and referral rates before and after establishing a psychiatric ward, and to evaluate the impact of ward on patient’s care outcomes. This quasi-experimental pre-post study analyzed data from patients treated at a tertiary care hospital between 2019 and 2024. Demographic and clinical characteristics, including psychiatric and physical conditions, referral rates, and outcomes, were compared before and after the psychiatric ward’s establishment in October 2022. Interrupted time series analysis assessed referral trends, and descriptive statistics compared patient characteristics and treatment outcomes. From this study, a total of 783 patients were recruited, with 497 treated before and 286 after the ward’s establishment. The primary diagnoses shifted from substance use disorders (78.7% to 34.9%) to schizophrenia (6.4% to 33.2%), while mood disorders increased from 14.9% to 24.1%. Many patients presented with coexisting physical conditions requiring care. The median length of stay increased from 2 days (IQR: 1-4) to 13 days (IQR: 7-23, p<0.001), while readmission rates remained stable (1.6% vs. 2.8%, p=0.258). Clinical outcomes improved, with reductions in psychiatric symptoms and SAVE scores at discharge. Referral rates trended downward with a non-significantly immediate reduction (change=-8.64, 95% CI: -234 to 307,p=0.848) and no significant change in trend after the ward’s establishment (slope change=-1.16, 95% CI:-6.33 to 4.01, p=0.656). The establishment of psychiatric wards in regional and general hospitals has significantly improved patient care outcomes, allowing for comprehensive treatment addressing both physical and mental health needs through multidisciplinary teams. Patient care outcomes have also markedly improved, while referral rates to specialized facilities have trended to decline. Expanding psychiatric units and resources in regional and general hospitals has improved patient access and care continuity. This integrated model enhances treatment efficacy and reduces mental health stigma by incorporating psychiatric care into general healthcare settings.